The Truth Commissions and Reports, between the expert voice and the real experience. The case of Guatemala, Memory of Silence - Astorga Sánchez, Leonardo (2021)
This abstract aims to analyze the role played by the report Guatemala, Memory of Silence as an instrument and mechanism of resistance and fight against oblivion and impunity. The abstract begins with a journey through recent Guatemalan history in order to establish a context of the facts collected and analyzed in the report then go to analyze it and how it is constructed. It is proposed that the participation of experts in the selection, analysis and writing of the report starts from an official position that legitimizes the discourse that is constructed.